POTENSI FITNAH HARTA DALAM KEHIDUPAN DI DUNIA PERSPEKTIF QS. AL-KAHFI: 46 - Shodiq Ahmad, Mohammad (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2022)
Contains a brief description of the reasons for writing articles (research), approaches and methods Life is a test and a trial. Whoever the person, in carrying out his life will surely face various slander. And no human being is free from the fitnah that accompanies it. More specifically, with the slander of property. In this case, the intended slander is a temptation. Where wealth will be a temptation for humans in carrying out the journey of life. Upper class people will face the temptation of wealth, even though they have found a lot of price, they will still be tempted by it. Then, middle class humans also experienced the same thing. Moreover, those who are in the poverty line and all in need, to the point that it is feared that poverty will fall into disbelief. Like being rich, there will also be many slipping from the right path, if someone is too tempted by this slander of wealth. This study aims to determine the extent to which the potential of the treasure tempts humans, and how the human attitude towards the temptation or slander of the treasure. Next, explore some of the instructions of the Qur'an, and how Muslims spend the gift of wealth in the right way and be pleased with Allah swt. This research uses qualitative research methods, namely library research, where the author has tried to find data that is relevant to the problems being raised and what is happening in people's lives today, by taking the literature that discusses this. From various points of view of the commentators, both classical and contemporary, on the study of QS. Al-Kahf: 46. The results of the research analysis show that the Qur'an is a guide to the life of a Muslim. It is from these instructions that will guide Muslims in fortifying the various slanders they face, especially slander and the temptation of wealth. Where treasure has the potential to tempt and tempt mankind. But on the other hand, Allah SWT gives instructions so that the property will have the potential to deliver its owner into savings for his good deeds, which will be reaped in the afterlife. So by inviting back to Allah's guidance, it will be found that with that capital it can actually lead someone to further pleasures in the hereafter.